Analisis Financial Distress dengan Metode Springate pada Perusahaan Pariwisata, Restoran dan Hotel Tahun 2019-2024 - Zulhelmi, Zulhelmi; Mukmin, Mas Nur; Kusuma, Indra Cahya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the Springate method in predicting financial distress in Tourism, Restaurant, and Hotel companies listed on the Indonesia Stock Exchange during the 2019-2024 period. The method used in this research is Springate's financial ratios, with data processed using Microsoft Excel. This research is a descriptive quantitative study. The population for this study consisted of 43 companies. The sampling technique used was purposive sampling, resulting in a sample size of 20 companies. The data source was secondary data in the form of annual financial reports from the selected companies for the 2019-2024 period. Based on the S-Score analysis of the sample companies, a significant trend of financial distress was found. In 2019, 14 out of 20 companies experienced financial distress. This situation worsened drastically in 2020, where all sample companies were identified as financially distressed, indicating the major impact of the COVID-19 pandemic and the continuing challenging conditions in 2021. Although there was an improvement post-pandemic, with 4 companies not experiencing financial distress in 2022 and 6 companies not experiencing financial distress in 2023, the financial condition of this sector remains unstable. Fluctuations in 2024, with only 5 companies not experiencing financial distress, indicate that the financial stability of this sector has not fully recovered and remains vulnerable to various factors.